The influence of non-financial compensation on attitude towards the job of support staff : comparison between public and private sector - Lim, Bo Nie. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Thi study aims to identify the influence of non-financial compensation on attitude towards the job of support staff. A comparison between public and private sector has been made in order to clearly identify its influence on job attitude. Simple Random Sampling method was used to identify the number of sample for this study. There are 37 respondents gathered from the public sector (JKR), while 35 respondents from the private sector (CMSB). A set of questionnaires were distributed to the respondents in data collection process. This study consists of six hypothesis and was analyzed using Inference and Descriptive Statistic to determine the relationship between the variables and the dominant factor influencing job attitude. The dependent variable is attitude towards the job, while the independent variables are recognition, advancement opportunities, comfortable working conditions and competent supervisor. The findings of this study revealed that all of the independent variables have a significant relationship on the dependent variable. In other words, all of the selected nonfinancial compensation elements have influence on the job attitude of the SHpport staff in both organizations. This study also shows that none of the respondents rated themselves as having low attitude towards their job. Advancement opportunities were found to be the dominant factor in influencing the job attitude of at lKR. Meanwhile, competent supervisor was the dominant factor in CMSB. Hence, both organizations should take into consideration all of the elements in this study as they have been proved to have significant influence on attitude towards the job.